2007
DOI: 10.1158/1078-0432.ccr-06-2937
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Macrophage Colony-Stimulating Factor–Secreting Allogeneic Cellular Immunotherapy for Hormone-Refractory Prostate Cancer

Abstract: Purpose: This trial evaluated the safety, clinical activity, and immunogenicity of an allogeneic cellular immunotherapy in 55 chemotherapy-naI« ve patients with hormone-refractory prostate cancer (HRPC). The immunotherapy, based on the GVAX platform, is a combination of two prostate carcinoma cell lines modified with the granulocyte macrophage colony-stimulating factor (GM-CSF) gene. Experimental Design: HRPC patients with radiologic metastases (n = 34) or rising prostatespecific antigen (PSA) only (n = 21) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(149 citation statements)
references
References 34 publications
1
146
0
1
Order By: Relevance
“…44 GM-CSF results in recruitment of DCs, which then present antigens to T-cells invoking an anti-tumour cascade of immune responses. The whole tumour cell is used as the antigen, rather than just the PAP, as in sipuleucel-T, facilitating both humoural and cellular immune responses.…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 GM-CSF results in recruitment of DCs, which then present antigens to T-cells invoking an anti-tumour cascade of immune responses. The whole tumour cell is used as the antigen, rather than just the PAP, as in sipuleucel-T, facilitating both humoural and cellular immune responses.…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
“…The whole tumour cell is used as the antigen, rather than just the PAP, as in sipuleucel-T, facilitating both humoural and cellular immune responses. Initial phase I/II studies confirmed safety, clinical activity, and immunogenicity; 44,45 however, two phase III studies (VITAL-1, VITAL-2) 46 were closed early due to futility analysis.…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
“…The regimen consisted of two allogeneic cell lines (PC3, LNCaP) modified to secrete GM-CSF. 73 PC3 is derived from prostate cancer bone marrow metastases and is castration resistant. 74 The LNCaP cell line derived from prostate cancer lymph node metastases is hormone sensitive, and expresses numerous prostate-associated antigens.…”
Section: Prostate Cancermentioning
confidence: 99%
“…The third is Dendreon's Provenge Ò , which is the only therapeutic cancer vaccine approved by the USA. regulatory Agency FDA for the treatment of metastatic hormone-refractory prostate cancer [5,6]. Although this vaccine represents an important proof of concept, it is able to induce a limited improvement in overall survival, with associated elevated costs of production, which indicates that significant improvements are needed.…”
Section: Gennaro Cilibertomentioning
confidence: 99%